Profitability and Feasibility Analysis of Traditional Beef Cattle Fattening Business: A Case Study of Blang Rimeh Farmers Group in Pidie Regency - Khalidin, Khalidin; Subagyo , Djoko; Rahayu, Sri; Masrianto, Masrianto; Yani, Abrida (Journal of Agriculture, 2025)
Cattle fattening is an important livelihood for rural farmers in Indonesia, particularly in regions such as Pidie District, where small-scale livestock management contributes significantly to household income. However, limited capital, traditional management practices, and lack of economic feasibility information often hinder farmers from optimizing their productivity and profit. This study aims to analyze the profitability and feasibility of the cattle fattening business operated by the Blang Rimeh Farmers Group in Pulo Seunong Village, Tangse Subdistrict, Pidie Regency, as a basis for determining whether the business is viable for further development. The research was conducted from March to April 2024 using a survey approach with a census of all 11 group members as respondents. Data were collected through observation, interviews, and questionnaires. Profitability analysis was calculated using the income formula (? = TR ? TC), while feasibility was assessed through the Revenue/Cost (R/C) ratio and Return on Investment (ROI). The cattle fattening activities were found to be traditional in scale, with each farmer raising an average of one head and relying solely on fresh forage without the use of concentrate supplementation. The analysis revealed an average income of IDR 2,096,061 per person per period, a return on capital (R/C) ratio of 1.11, and an ROI of 11%. These values suggest that, despite the simplicity of management practices, the business generates a positive return and provides significant financial benefits to farmers.The cattle fattening business in the Blang Rimeh Farmers Group is profitable and feasible to pursue. Strengthening feeding management, improving facilities, and enhancing technical knowledge may further increase productivity and profitability.